RELEVANSI NILAI LEVERAGE, DIVIDEN, DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN-PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2014-2016 - Ericson Wijaya, Amelia Sandra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2018)
Financial statements that have good value relevance can be a benchmark for an enterprise's value increase that can increase stock prices. Accounting information in the form of financial statements is expected to describe the actual condition of the company. Accounting information such as financial statement hopefully can describe the actual condition of the company.This research aims to analyze the influence of the value relevance of accounting information contained in leverage, dividend, and profitability to stock prices. Clean surplus theory is talking about predicting and analyzes function of financial statement. Market efficient theory is talking about quality of the information itself. And signaling theory is talking about how the information impacts the community. The object of this study was 25 companies who registered in manufacturing industries that listed at Indonesia Stock Exchange for the year 2014-2016. Tools that be used for data analysis in this research are pooling, classical assumption, statistic descriptive test, F-test, t-test, and coefficient determination of R square by using SPSS 20.0 . This research shows that leverage doesn’t have a value relevance to the share price, dividend doesn’t have a value relevance to the share price, and profitability has a value relevance to the share price. Keyword : Value Relevance, Leverage, Dividend, Profitability